Distribution and abundance of cichlids in the New Calabar River, Nigeria - Olaniyi Alaba Olopade; Henry Eyina Dienye (Journal of Fisheries, 2018)
This study was conducted to study the distribution, abundance and diversity of the cichlids in the New Calabar River, Nigeria. A total of 1073 cichlids belonging to ten species and seven genera (Coptodon guineensis, C. zillii, C. dageti, Pelmatolapia mariae, Hemichromis fasciatus, Pelvicachromis taeniatus, Chomidotilapia guntheri, Tylochromis sudanensis, Sarotherodon galilaeus and S. melanotheron) were collected from three sampling stations between February and July, 2017. The most abundant species, in terms of number, was C. guineensis comprising 33.3% of all the number of species recorded followed by C. zillii (19%) and S. galilaeus (16.7%) while in terms of weight the dominant cichlids were C. guineensi   (38.4%),  C. zillii (19.6%) and S.  melanotheron (12.9%). Five species, C. guineensis, S. melanotheron, S. galilaeus, C. dageti and C. zillii were recorded throughout the months of study. The Shannon-Weaver diversity index was found the highest (1.5) at Station 1 and the lowest (0.93) at Station 3 while Pielou’s evenness index was the highest (0.77) at Station 1.